Mechanotransduction and nuclear function. (June 2016) - Graham, David M; Burridge, Keith
Abstract : Many signaling pathways converge on the nucleus to regulate crucial nuclear events such as transcription, DNA replication and cell cycle progression. Although the vast majority of research in this area has focused on signals generated in response to hormones or other soluble factors, the nucleus also responds to mechanical forces. During the past decade or so, much has been learned about how mechanical force can affect transcription, as well as the growth and differentiation of cells. Much has also been learned about how force is transmitted via the cytoskeleton to the nucleus and then across the nuclear envelope to the nuclear lamina and chromatin. In this brief review, we focus on some of the key proteins that transmit mechanical signals across the nuclear envelope.